#SELFIES at the 2016 Rio Olympics: Comparing Self-Representations of Male and Female Athletes from the U.S. And China. Issue 2 (3rd April 2019) - Xu, Qingru; Armstrong, Cory L.
Abstract : Social media provides athletes an efficient platform on which to build and maintain their online image. Applying the self-representation theory of Goffman (1959), this study explored the gendered differences between the self-portrayals of U.S. and Chinese athletes. Findings suggest that hegemonic gender norms still had a strong hold on Chinese athletes' self-disclosure, whereas minimal gender differences emerged between male and female U.S. athletes. Results suggested that cultural background had a substantial impact on self-representation for all participants. Although athletes might claim agency when presenting themselves on social media, the practice of self-portrayal should be examined within specific cultural contexts.